2008
DOI: 10.1261/rna.1020708
|View full text |Cite
|
Sign up to set email alerts
|

Initiating translation with D-amino acids

Abstract: Here we report experimental evidence that the translation initiation apparatus accepts D-amino acids ( D aa), as opposed to only L-methionine, as initiators. Nineteen D aa, as the stereoisomers to their natural L-amino acids, were charged onto initiator tRNA fMet CAU using flexizyme technology and tested for initiation in a reconstituted Escherichia coli translation system lacking methionine, i.e., the initiator was reprogrammed from methionine to D aa. Remarkably, all D aa could initiate translation while the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
88
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
3

Relationship

3
7

Authors

Journals

citations
Cited by 115 publications
(89 citation statements)
references
References 35 publications
1
88
0
Order By: Relevance
“…Several attempts to recode the N-terminus of proteins with ncAAs have been pursued, mostly using in vitro approaches. [64][65][66][67][68] Interestingly, several Met analogues are known to work in protein initiation in vivo, indicating that they are formylated by methionyl-tRNA fMet formyltransferase (FMT) and recognized by the initiation factors (IFs). [69] In addition, their N-terminal processing is attenuated [69] and can be regulated by changing the identity of the second amino acid in the protein sequence.…”
Section: Site-specific Reassignment Of the Aug Codonmentioning
confidence: 99%
“…Several attempts to recode the N-terminus of proteins with ncAAs have been pursued, mostly using in vitro approaches. [64][65][66][67][68] Interestingly, several Met analogues are known to work in protein initiation in vivo, indicating that they are formylated by methionyl-tRNA fMet formyltransferase (FMT) and recognized by the initiation factors (IFs). [69] In addition, their N-terminal processing is attenuated [69] and can be regulated by changing the identity of the second amino acid in the protein sequence.…”
Section: Site-specific Reassignment Of the Aug Codonmentioning
confidence: 99%
“…When elongation tRNAs carrying D-amino acids are presented to the ribosome in vitro they are incorporated extremely poorly, but incorporated nevertheless (Yamane et al 1981;Heckler et al 1988). It has recently been found that peptide synthesis can be effectively initiated with D-amino acids (Goto et al 2008). In addition, by introducing mutations in the PTC region and/or other nearby regions of the 23S rRNA, it was possible to obtain enhanced tolerance of D-amino acids in vitro (Starck et al 2003;Tan et al 2004;Dedkova et al 2003 and2006).…”
Section: Chirality and The Ribosomementioning
confidence: 99%
“…Additionally, diverse kinds of N-acylamino acids, such as L-and D-amino acids 23,24 and exotic peptides 26 have been used for the initiation to express Nterminal-modified peptides. In the combination of the above techniques with appropriate chemical reactions, unique macrocyclic peptides can be synthesized.…”
Section: 41mentioning
confidence: 99%